The treatment of combatants and insurgents under the law of armed conflict - Crawford, Emily, Dr. (Oxford : Oxford University Press, 2010)
This book looks at why international law continues to make the legal distinction between persons who participate in an international or an internal armed conflict. Drawing on legal precedent, legal theory, & the situation in Guantanamo Bay, it argues that it is time for the law of armed conflict to be applied more uniformly.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Combatants and noncombatants (International law); Prisoners of war